A chronology of the Pre-Columbian Paracas and Nasca cultures in South Peru based on AMS 14C dating - Unkel, Ingmar; Kromer, Bernd; Reindel, Markus; Wacker, Lukas; Wagner, Günther A. (Radiocarbon, 2007)
The people of the Paracas and Nasca cultures, the creators of the famous geoglyphs, lived in the desert of the southern coast of Peru between about 800 BC and AD 650. The archaeological chronology of these cultures has been based almost exclusively on a sequence of ceramic styles. The absolute dating of some of the style phases was supported by a few radiocarbon dates (Rowe 1967). Here, we present an absolute chronology of the Paracas and Nasca cultures based on 14C dating of more than 100 organic samples from settlement and tomb relics, as well as on material derived from geoglyph sites in the Nasca/Palpa region (south Peru). The main focus has been on Nasca period settlement centers near Palpa, Los Molinos and La Muña, the Paracas period site of Jauranga, and the Initial period site of Pernil Alto. Most of the 14C samples were dated at the accelerator mass spectrometry (AMS) facility of the ETH Zurich (Switzerland). The targets were produced in the newly built graphitization line at the Heidelberg 14C laboratory (Germany). Clay (adobe) bricks, which are quite a common building material in Peru, were successfully tested to be used for AMS 14C dating of adobe architecture in Peruvian archaeology.